The Effect of Company Size, Auditor Change, and Audit Committee Gender on Audit Delay (Empirical Study of Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange 2020-2024) - Khaerun Nisa, Nina; Qadarti Anjilni, Ratih (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
The purpose of this study was to determine and obtain empirical evidence regarding the influence of company size, auditor turnover, and audit committee gender to audit delay. This study used an associative quantitative approach. Data collection used purposive sampling from a sample of banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Based on the model testing results, the best model was the Random Effects Model. The study concluded that company size, auditor turnover, and audit committee gender simultaneously influenced audit delay. Company size partially influenced audit delay, auditor turnover had no partial effect on audit delay, and audit committee gender partially influenced audit delay.